Minimal Realization Plus Current Output CC-based Biquad Circuit - Sompong Wisetphanichkij; Krit Angkeaw; Napat Sra-ium (My University, 2023)
This paper presents a minimal design of biquad circuit using only one plus current output type-II current conveyor (CCII), one differential voltage current conveyor (DVCC) and grounded passive components. The circuit enables all 5 basic filter types, low-pass (LP), band-pass (BP), high-pass (HP), band-stop (BS) and all-pass (AP) implementation by the selection and addition of the input and output currents with no component matching constraints. Moreover, the circuit parameters $\omega$0 and Q can be set simply by adjusting the circuit components. The proposed biquad circuit performance has very low sensitivity to circuit components due to its simple structure and small number of devices (2 active and 4 grounded passive components). This allows the circuit to work at high frequencies. The performance of the proposed topology was evaluated through PSPICE simulator using the 0. 1S$\mu$m CMOS technology from the Taiwan Semiconductor Manufacturing Company (TSMC).
Keywords: Analog and Mixed-Signal Circuit Design; Low-power high-performance VLSI design; Advancements in Semiconductor Devices and Circuit Design